Kointegrasi dan kausalitas pasar saham Big 5 ASEAN: Tax Amnesty gelombang I - Loe Irene Kusuma; Noviana Anggun; Gesti Memarista (STIE Perbanas Surabaya, 2016)
The first batch of Tax Amnesty policy in Indonesia can affect the economy in other countries because of international cooperation, especially in ASEAN. This study tried to see the cointegration and the causality between stock market indices in the Big 5 ASEAN countries before the policy (October 5th 2015-July 01st 2016), during the policy (July 03rd 2016 - September 30th 2016), and after the policy (October 03rd 2016 - November 04th 2016). The data used is the closing value of daily stock market indices of the Big 5 countries in the ASEAN during those periods. The results showed that there is no cointegration relationship before and during the implementation of the first batch of Tax Amnesty policy. Otherwise, there is a cointegration relationship after the policy implemented. In addition, there is a causality relationship for the stock market index before the policy, such as Indonesia (JKSE) affects Singapore (STI) and Thailand (SET), while the Philippines (PSEi) affects Thailand (SET). During the policy, Thailand (SET) affects Indonesia (JKSE) and the Philippines (PSEi), while the Philippines (PSEi) affects Thailand (SET). After the policy, Thailand (SET) and Singapore (STI) affect each other, while Thailand (SET) affects Malaysia (KLCI).